Optimal Power and Modulation Adaptation Policies with Receiver Diversity over Rayleigh Fading Channel - Muhammad Imran Tariq; Razvan Beuran; Yoichi Shinoda (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Efficient bandwidth utilization is paramount in wireless communication systems, particulary in fadingenvironments, since fading is one of the major constraints that impair communication in wireless systems.The bandwidth efficiency of a wireless communication system can be enhanced significantly by employingpower and modulation adaptation policies with diversity combining gain. In this work, first we examine ananalytically-derived solution for Maximum Combining Ratio (MRC) diversity technique for the capacity perunit bandwidth. Then, we design an adaptive transmission system to utilize the diversity combining gain whileretaining the target BER by adapting power and constellation size using continuous power, channel inversionwith fixed rate and continuous power and disrecte-rate. By considering the effect of diversity combininggain, the designed system yields a reasonable spectral efficiency with respect to target BER that grows asthe number of diversity levels increase. Furthermore, the presented results show continuous power anddiscrete-rate adaptation policy reduces probability of outage unlike its achieved spectral efficiency is closeto other selected policies, which ratifies the optimized switching thresholds and makes it best candidate forimperfect channel conditions.